A new genus within the tribe Lonchaeini (Diptera, Lonchaeidae) based on two species from the Neotropics - Macgowan, Iain (Zootaxa, 2022)
Hydrolysa gen. nov. is erected within the tribe Lonchaeini to include Central American species which possess distinctive and unique male genitalia. Two species are described within this new genus, namely Hydrolysa tanetzensis MacGowan sp. nov. and Hydrolysa oaxacana MacGowan sp. nov. A revised key to the genera within the Lonchaeini and a key to males of Hydrolysa is provided.